2017
DOI: 10.1186/s12889-017-4566-3
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of injury-related mortality on life expectancy in Zhejiang, China based on death and population surveillance data

Abstract: BackgroundLife expectancy is a statistical measure of the average time an organism is expected to live. The purpose of this study was to evaluate the impact of injury-related mortality on life expectancy in Zhejiang Province.MethodsOur study used standard life tables to calculate life expectancy and cause-removed life expectancy based on mortality data from the Zhejiang Chronic Disease Surveillance System.ResultsLife expectancy of residents in Zhejiang was 77.83 years in 2013, with females having a higher life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Injuries mainly include road traffic injuries, suicide, falls, and drowningdrowning [2]. Life expectancy in developing countries is reduced by 1.19 years due to injury [3]. In China [4], the proportion of injury deaths among 0-14 years of children in China rose from 18.69% in 2004 to 21.26% in 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Injuries mainly include road traffic injuries, suicide, falls, and drowningdrowning [2]. Life expectancy in developing countries is reduced by 1.19 years due to injury [3]. In China [4], the proportion of injury deaths among 0-14 years of children in China rose from 18.69% in 2004 to 21.26% in 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to suggest that widowed older people should be investigated separately rather than in conjunction with those who are single or divorced. Despite women having longer life expectancies than men [26], we found that high-aged older people men and women had similar high widowhood rates. This nding suggests that it is more di cult to continue marriage at an advanced age than to extend the life of high-aged older people individuals.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, it is reasonable to suggest that widowed older persons should be investigated separately rather than in conjunction with single or divorced elderly people. Despite women have longer life expectancies than men [26], we found that high-age elderly men and women had similar high widowhood rates. This finding suggests that it is more difficult to continue marriage at an advanced age than to extend life itself for both long-lived men and women.…”
Section: Discussionmentioning
confidence: 57%